Dynamic process and impact force evolution characteristics of debris flow entraining irregular boulders impacting check dams - Wang, Yugang; Gong, Hongsheng; Chen, Gang; Sui, Sugang; Ma, Lin (Frontiers in Earth Science, 2026)
In studies on the impact forces of debris flow boulders, most scholars simplify boulders as spheres, thereby neglecting the influence of their irregular shapes. Therefore, this study adopts a coupled SPH-FEM method to establish a numerical flume model for investigating the impact of irregular boulders in debris flows on check dams. The validity of this method is verified through field flume tests. Systematic simulations are conducted to analyze the interactions among the slurry, single boulders, multiple boulders, and check dams. The results indicate that with the increase in slope gradient and boulder mass, the boulder impact forces increase significantly, while the buffering effect of the slurry gradually weakens. During the movement of multiple boulders, collisions and energy exchange between boulders lead to a reduction in their impact forces compared to those of single boulders. Specifically, in the movement of single and multiple boulders, the peak impact force of Boulder 1 decreases by approximately 12.97%–27.50%, and that of Boulder 2 decreases by about 14.60%–30.87%. The research findings provide a theoretical basis for the dynamic response analysis of rigid check dams and the design of engineering protection under debris flow hazard conditions.